2022
DOI: 10.3390/machines10020118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Eddy Current Loss and Structure Design with Magnetic-Thermal Coupling for Toothless BLDC High-Speed PM Motor

Abstract: Brushless direct current (BLDC) permanent magnet (PM) synchronous motors are in high demand for ventilator applications owing to their high speed, high efficiency, and other significant features. However, it has become an important problem in eddy current loss calculations with high-speed motors, which leads to low motor (ventilator) life and PM demagnetization. This paper focuses on the eddy current loss calculation and the structure improvement design for the two-pole 90 W, 47,000 r/min toothless BLDC motor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…FEM simulation entails executing a comprehensive design algorithm that incorporates a step-bystep design process, access to data libraries such as standard wire gauges and magnetic material properties, along with interactive input and output capabilities for enhanced functionality [41,42]. The design of a PM motor control system utilizes the MagNet (v7.1.1) software, specifically focusing on enhancing speed control for these motors [43,44]. It provides a comprehensive overview of the system's functionality and design approach.…”
Section: Introductionmentioning
confidence: 99%
“…FEM simulation entails executing a comprehensive design algorithm that incorporates a step-bystep design process, access to data libraries such as standard wire gauges and magnetic material properties, along with interactive input and output capabilities for enhanced functionality [41,42]. The design of a PM motor control system utilizes the MagNet (v7.1.1) software, specifically focusing on enhancing speed control for these motors [43,44]. It provides a comprehensive overview of the system's functionality and design approach.…”
Section: Introductionmentioning
confidence: 99%
“…BLDCM is a trapezoidal wave brushless motor that uses Hall sensors to detect the rotor position. It is controlled by a six-step commutation method of the stator winding, which is based on the rotor position [1][2][3]. The BLDCM offers several advantages, including a simple structure, excellent speed regulation performance, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to calculate the rotor eddy current loss of the PM motors [1][2][3][4][5][6][7]. For the axial flux permanent magnet motor, the 2D analytical model cannot accurately calculate the eddy current loss of permanent magnets.…”
Section: Introductionmentioning
confidence: 99%
“…After verification, it was found that this method can significantly improve the efficiency of motor design optimization. Du et al [4] developed a multi-parameter improvement method for high-speed motor design. In part of the winding design, after a large amount of data analysis, the relationship between the two parameters and eddy current loss is summarized.…”
Section: Introductionmentioning
confidence: 99%